2006
DOI: 10.1002/gps.1437
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study regarding conversion from mild memory impairment to dementia in a Japanese community

Abstract: The rate at which subjects with MMI/ND whose conditions shifted to dementia was the same as the rate that subjects with mild cognitive impairment (MCI) shifted to dementia in a previous report. It would be useful to identify groups of high-risk individuals for dementia by simple diagnostic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 35 publications
(41 reference statements)
0
49
0
Order By: Relevance
“…In Germany, the Leipzing Longitudinal Study Of Aged (LEILA 75þ) reported the prevalence of MCI and modified-MCI which were 3.1 and 5.1%, respectively (Anja et al, 2003). In Japan, at baseline 104 subjects with mild memory impairment/not dementia (MMI/ND) were selected from 1162 community dwellers aged over 65 years and the prevalence was 8.95% (Ishikawa et al, 2006). In Canada, the most commonly used case definition of MCI yielded a population prevalence estimate of 1.03% from the Canadian Study of Health and Aging.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, the Leipzing Longitudinal Study Of Aged (LEILA 75þ) reported the prevalence of MCI and modified-MCI which were 3.1 and 5.1%, respectively (Anja et al, 2003). In Japan, at baseline 104 subjects with mild memory impairment/not dementia (MMI/ND) were selected from 1162 community dwellers aged over 65 years and the prevalence was 8.95% (Ishikawa et al, 2006). In Canada, the most commonly used case definition of MCI yielded a population prevalence estimate of 1.03% from the Canadian Study of Health and Aging.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported findings in multiple publications, particularly those from large databases such as the CSHA. Where possible we excluded studies reporting subsamples and included only the main analysis (13,(32)(33)(34)(35). We included data from randomized trials but only using placebo data as this was considered more representative of the natural history of MCI.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Within the MCI group there are various subgroups, with the amnestic Mild Cognitive Impairment (aMCI) group characterized by a single memory disorder [2]. This group is at higher risk for converting to AD compared to healthy subjects and other MCI subtypes such as non-amnestic MCI [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%